THE EXAMINATION OF THE SEVENTH GRADE STUDENTS’ VISUAL LITERACY LEVELS - Sevda GÖKTEPE YILDIZ (Fırat University, 2019)
Literacy can be expressed in general as information and competencies that required about a discipline. Visual literacy is one of the areas. Visual elements are found in almost every mathematics topics. Graphics, diagrams, concept maps, and tables are often used as the part of the teaching-learning process. Therefore, the development of students' visual literacy skills is an important issue for their mathematics academic achievement. The purpose of the study was to examine the seventh grade students’ visual literacy levels with regard to various variables. The variables examined in this study were mathematics academic achievement, students’ intelligence types. Besides, gender differences on visual literacy levels were investigated. Survey model was determined as the method of the study. Multiple intelligences types scale and visual literacy competencies scale were used for data collection tools. In addition, students’ mathematics course scores in their school report were evaluated as their mathematics academic achievement. Seventy-six students from two different public schools were participated in. Obtained data were analysed quantitatively. Results revealed that there were no significance differences between students’ mathematics academic achievement and their visual literacy levels and their intelligence types and visual literacy levels. However, there were more students that have social-interpersonal intelligence and logical-mathematical intelligence. Besides, meaningful differences were determined between students’ visual literacy competencies according to their genders. Implications for further studies were presented related to these results.